Physical properties and evolution of the eclipsing binary system XZ canis minoris - Poochaum R. (2014)
This research aims to study the eclipse binary system so that its physical properties and evolution can be determined and used as an example to teach high school astronomy. The study of an eclipsing binary system XZ Canis Minoris (XZ CMi) was done at Sirindhorn Observatory, Chiang Mai University using a 0.5-meter reflecting telescope with CCD photometric system (2184×1417pixel) in B V and R bands of UVB System. The data obtained were used to construct the light curve for each wavelength band and to compute the times of its light minima. New elements were derived using observations with linear to all available minima. As a result, linear ephemeris is HDJminI=.578 808 948±0.000 000 121+2450 515.321 26±0.001 07E, and the new orbital period of XZ CMi is 0.578 808 948±0.000 000 121day. The values obtained were used with the previously published times of minima to get O-C curve of XZ CMi. The result revealed that the orbital period of XZ CMi is continuously decreased at a rate of 0.007 31±0.000 57sec/year. This result indicates that the binary stars are moving closer continuously. From the O-C residuals, there is significant change to indicate the existence of the third body or magnetic activity cycle on the star. However, further analysis of the physical properties of XZ CMi is required. © 2010 American Institute of Physics.